PEMBUATAN KATALIS H-ZEOLIT DENGAN IMPREGNASI KI/KIO3 DAN UJI KINERJA KATALIS UNTUK PRODUKSI BIODIESEL - Lukman Hakim Firdaus; Adit Rizky Wicaksono; W Widayat (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
H-Zeolite catalysts synthesized from natural zeolite include chemical treatment process stages, screening, washing, impregnation KI/KIO3 and physical treatment. The objective of this research is to study characteristics of catalyst that was impregnated KI / KIO3 with surface area analysis, X-Ray Diffraction (XRD) and performance test of catalyst for production of biodiesel. The results showed that the surface area of ​​the catalyst by 27.236 m2/ g at a concentration of 5% KI. XRD analysis of the value obtained at 2-θ peak at 23.627o zeolite indicating that KI was impregnated on H-zeolite catalyst. The catalyst was tested for production of biodiesel using palm oil with conventional methods for 3-hour temperature of 70-80oC. The Result for conversion Fatty Acid Methyl Ester (FAME) had maximum value on 87.91% at a concentration of catalyst impregnation variable KIO3 5%.